2012
DOI: 10.1097/brs.0b013e318252ccbe
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Changes in Spinal Rod Contour in Adolescent Idiopathic Scoliosis

Abstract: We found a significant difference between pre- and postoperative rod contour, particularly for concave rods. Rod overcontouring (by ~20° for concave rod) resulted in high degrees of correction without loss of sagittal alignment. The resulting deformations are likely associated with substantial in vivo deforming forces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 26 publications
5
54
0
Order By: Relevance
“…This finding indicated that concave-side rather than convex-side screw density had an impact on TK restoration. It supports the importance of concave-side implant density on TK restoration reported by Cidambi et al 5 and La Rosa et al 15 A possible explanation could be that the increased friction at the screw-rod interface that occurs with higher screw density would prevent flattening of the contoured rod in the sagittal plane after rod rotation (Fig. 1).…”
supporting
confidence: 69%
See 4 more Smart Citations
“…This finding indicated that concave-side rather than convex-side screw density had an impact on TK restoration. It supports the importance of concave-side implant density on TK restoration reported by Cidambi et al 5 and La Rosa et al 15 A possible explanation could be that the increased friction at the screw-rod interface that occurs with higher screw density would prevent flattening of the contoured rod in the sagittal plane after rod rotation (Fig. 1).…”
supporting
confidence: 69%
“…Theoretically, a larger and stiffer rod would have greater ability for correction in the coronal and sagittal planes, based on biomechanical studies. 5,16,36 However, results from different clinical studies have not been in accordance. For coronal plane correction, insufficient evidence was found to support the hypothesis that better correction would be provided by high rod stiffness.…”
mentioning
confidence: 70%
See 3 more Smart Citations